A novel rocket-borne ion mass spectrometer with large mass range: instrument description and first-flight results - Stude, Joan; Aufmhoff, Heinfried; Schlager, Hans; Rapp, Markus; Arnold, Frank; Strelnikov, Boris (Katlenburg-Lindau : European Geosciences Union, 2021)
We present a novel rocket-borne ion mass spectrometer named ROMARA (ROcket-borne MAss spectrometer for Research in the Atmosphere) for measuring atmospheric positive and negative ions (atomic, molecular and cluster ions) and positively and negatively charged meteor smoke particles. Our ROMARA instrument has, compared to previous rocket-borne ion mass spectrometers, a markedly larger mass range of up to m=z 2000 and a larger sensitivity, particularly for meteor smoke particle detection. The major objectives of this first ROMARA flight included the following: a functional test of the ROMARA instrument, measurements between 55 and 121 km in the mass range of atmospheric positive and negative ions, a first attempt to conduct mass spectrometric measurements in the mass range of meteor smoke particles with mass-to-charge ratios up to m=z 2000, and measurements inside a polar mesospheric winter echo layer as detected by ground-based radar. Our ROMARA measurements took place on the Arctic island of Andøya, Norway, at around noon in April 2018 and represented an integral part of the polar mesospheric winter radar echo (PMWE) rocket campaign. During the rocket flight, ROMARA was operated in a measurement mode, offering maximum sensitivity and the ability to qualitatively detect total ion signatures even beyond its mass-resolving mass range. On this first ROMARA flight we were able to meet all of our objectives. We detected atmospheric species including positive atomic, molecular and cluster ions along with negative molecular ions up to about m=z 100. Above m=z 2000, ROMARA measured strong negative-ion signatures, which are likely due to negatively charged meteor smoke particles. © 2021 Author(s). publishedVersion